Analysis Of Existing Methods and Means of Monitoring the Technical Condition of Motor Vehicles (Eurasian Journal of Engineering and Technology, 2022)
Road transport is one of the important components of the forces for the successful development of the state economy. Road transport has not only economic but also strategic importance. This article discusses the analysis of existing methods and means of monitoring the technical condition of motor vehicles. A promising way to solve existing problems is to develop and implement a system that automates the collection and processing of diagnostic data. As a result, the content of the technical impact work performed on the diagnosed vehicle is recorded on the computer